An Analysis of Grammatical Errors Made by The Tenth Grade Students of SMAN 1 Cluring in Writing Recount Texts - Alisya, D.L.; Suarnajaya, I.W.; Ramendra, D.P. (Universitas Pendidikan Ganesha, 2021)
This study aimed to find out the types of grammatical errors made by the tenth grade students of SMA N 1 Cluring and classify the causes of the students’ errors that influenced their errors in writing recount texts. Descriptive qualitative research was used in this study to explore the data which focused on students’ grammatical errors in writing recount texts. The result of this study shows that there were 399 grammatical errors and consisting of 12 types of errors, namely omission of article, omission of preposition, omission of marker, omission of conjunction, simple addition, regularization error, alternating form, misordering, word choice, spelling, punctuation, and capitalization found in the students’ recount texts. The type of grammatical error mostly made by the students was alternating form which was 309 (77.44%) in total number. The most frequent source of errors which mostly influenced the students’ errors in their writings was intralingual transfer which had 325 (81.45%) of the total number of errors. However, the students still had problems in using grammatically correct sentences in paragraph, especially in writing recount texts. Furthermore, knowing the students’ grammatical errors in writing recount texts can be used as a basis for conducting remedial teaching. Keywords: Error Analysis; Grammatical Error; Recount Text.